TOXIC EFFECT OF UREA ON EARTH WORMS DETERMINED BY A SIMPLE PAPER CONTACT METHOD - DR. SURESHBABU (Global Journal of Plant and Soil Sciences, 2023)
Objective: Nowadays, the utilization of chemical fertilizer is hiked tremendously to achieve a high yield. The aim of this experimental research work is to confirm and detect the lethal or toxic effect of those chemical fertilizers on the earthworms which are the natural friend of soil as well as the farmer and also maintains the soil health by porosity and aeration. Methods: A simple paper contact method was adopted for the toxicity testing on the earthworms on the bed prepared using Petri plate and filter paper. Results: The lethal dose value was determined and the toxic effect of the urea on earthworm was calculated and represented using statistical inferences, and a scope of future study was created for the biochemical profiling toward the body degradation of the earthworms. Conclusion: From the above results, it may be concluded that the acute toxicity of urea on Eisenia fetida using a simple paper contact method was actually significant in confirming the toxic impending. The application of environmentally levelheaded doses of urea exposed the possible harmful effects on earthworms when comes in contact directly. Thus, in future, this method will be necessary to find an approach to establish the sensitivity of the earthworm’s acute toxicity before going for the evaluation in soil (i.e., acute and chronic toxicity tests in artificial soil sample).